Dexamethasone affects human fetal adrenal steroidogenesis and subsequent ACTH response in an ex vivo culture model - Melau, Cecilie; Gayete Mor, Berta; Lundgaard Riis, Malene; Nielsen, John E.; Dreisler, Eva; Aaboe, Kasper; Tutein Brenøe, Pia; Langhoff Thuesen, Lea; Juul Hare, Kristine; Mitchell, Rod T.; Frederiksen, Hanne; Juul, Anders; et al. (Frontiers in Endocrinology, 2023)
Administration of dexamethasone (DEX) has been used experimentally to suppress androgenization of external genitalia in 46,XX fetuses with congenital adrenal hyperplasia. Despite this, the prenatal biological mechanism-of-action of DEX on fetal outcome is not known. This study aimed to examine direct effects of DEX on human fetal adrenal (HFA) steroidogenic activity including possible effects on the subsequent response to ACTH-stimulation. Thus, Human fetal adrenal (HFA) tissue from 30 fetuses (1st trimester) were cultured ex vivo with A) DEX (10 uM) for 14 days, or B) DEX (10 uM) for 10 days followed by ACTH (1 nM) for 4 days. DEX-mediated effects on HFA morphology, viability, and apoptosis (immunohistochemistry), gene expression (quantitative PCR), and steroid hormone secretion (LC-MS/MS) were investigated. DEX-treatment caused decreased androstenedione (p<0.05) and increased cortisol (p<0.01) secretion suggesting that direct effects on the adrenal gland may contribute to the negative feedback on the hypothalamic-pituitary-adrenal axis in vivo. An altered response to ACTH stimulation in HFA pre-treated with DEX included increased androgen (p<0.05) and reduced cortisol production (p<0.05), supporting clinical observations of a temporary decreased ACTH-response following prenatal DEX-treatment. Additionally, the secretion of corticosterone was decreased (p<0.0001) following ACTH-stimulation in the initially DEX-treated HFAs. The observed effects suggest that prenatal DEX-treatment can cause direct effects on HFA steroidogenesis and in the subsequent response to ACTH-stimulation. This may indicate a requirement for careful monitoring of adrenal function in prenatally DEX-treated neonates, with particular focus on their mineralocorticoid levels.